Pathways of association between maternal haemoglobin and stillbirth: path-analysis of maternity data from two hospitals in England - Nair, M; Knight, M; Robinson, S; Nelson-Piercy, C; Stanworth, S; Churchill, D (BMJ Publishing Group, 2018)
Objective To investigate the mechanisms that link maternal haemoglobin concentration with stillbirth. Design A retrospective cohort analysis using anonymised maternity data from two hospitals in England. Setting The Royal Wolverhampton NHS Trust and Guy’s and St Thomas’ NHS Foundation Trust Study population 12,636 women with singleton pregnancies ≥24 weeks of gestation giving birth in the two hospitals during 2013-15. Method A conceptual framework of hypothesised pathways through birthweight-for-gestational age and maternal infection including potential confounders and other risk factors was developed and examined using path-analysis. Path-analysis was performed by fitting a set of regression equations using weighted least squares adjusted for mean and variance. Goodness-of-fit indices were estimated. Main outcome measures Coefficient of association (β) for relationship between each parameter, and direct, indirect and total effects via the postulated pathways. Results The path-model showed a significant adjusted indirect negative effect of maternal haemoglobin on stillbirth mediated via birthweight-for-gestational age (Standardised estimate (SE) = -0.01; 95% CI = -0.01 to -0.001; p=0.028). The effect through maternal infection was not significant at p<0.05 (SE= 0.001; 95% CI = -0.004 to 0.01; p=0.610). There was a residual direct negative effect of maternal haemoglobin on stillbirth (SE = -0.12; 95%CI -0.23 to -0.02; p=0.020) after accounting for the two pathways. Total indirect SE = -0.004; 95% CI -0.01 to 0.003; p=0.267; total direct and indirect SE = -0.13; 95% CI -0.23 to -0.02; p=0.016. The goodness-of-fit indices showed a good fit between the model and the data. Conclusion While some of the influence on risk of stillbirth acts through low birthweight-for-gestational age, the majority does not. Several new mechanisms have been suggested for how haemoglobin may be exerting its influence on the risk of stillbirth possibly involving genetic, epigenetic and/or alternative obstetric and nutritional pathologies, but much more research is needed.